Bioremediation of dyes: a brief review of bioreactor performance - Tiwari H.; Sonwani R.K.; Singh R.S. (My University, 2025)
It has long been known that the textile industry generates a massive amount of synthetic waste across the globe. Dye-containing wastewater is carcinogenic, mutagenic, recalcitrant, and xenobiotic. Several techniques have been developed for textile wastewater treatment. Most often, especially for dye-containing synthetic waste, bioremediation has now become one of the emerging techniques. Bioreactor, a common apparatus, whenever possible, may operate either continuously or in batches; has been extensively used for carrying out the hardest-to-meet biological reactions. The objective of this review is to emphasize a brief description of different bioreactors’ performance, their features, and shortcoming. Special emphasis has been laid out on Membrane Bioreactor, Fluidized Bed Bioreactor, Moving Bed Bioreactor, Packed Bed Bioreactor, Airlift Bioreactor, Stirred Tank Bioreactor, Fixed Bed Bioreactor, and Rotating Biological Contactor. The key findings of each bioreactor’s dye degradation performance have been reviewed. A brief discussion about recent trends in dye wastewater treatment has been depicted and based on the above facts future outlook is critically highlighted. A techno-economic assessment of bioremediation technology emphasizes its applicability for industrial scale. The review is expected to be beneficial to readers who are dealing with bioprocess, hybrid bioreactors, and designing bioreactors at a laboratory, pilot plant, and even on an industrial scale for the treatment of real textile waste. However, the selection criterion of a suitable bioreactor has relied on bioprocess engineering and economics. New technological advancements in the bioreactor have been discussed and Microbioreactor seems as a future outlook toward dye degradation. © 2023 Informa UK Limited, trading as Taylor & Francis Group.